Alih Aksara dan Analisis Ragam Bahasa Lontar Dharma Pawayangan Koleksi Dalang I Made Sidja - Wicaksana, I Dewa Ketut; Wicaksandita, I Dewa Ketut (Jayapangus Press, 2023)
Dharma Pawayangan is a holy book of puppeteers in Bali which is dynamic. The significance of this lontar is that its content is considered to contain structured and contextual knowledge of the theo-cultural activities of the Balinese puppeteers. However, the existing Lontar Dharma Pawayangan is still written in Balinese script and is in a condition that has not been digitized so that it is prone to damage and is often difficult to read. The purpose of this research is to translate one of I Made Sidja's lontar samples which is considered to have a tendency to signify complete content and to analyze the variety of languages that appear in it. Coding methods and literary studies are used to support linguistic theory and a hermeneutical approach to the analysis of this sacred literature. The results of the study found, first, the transliteration of one of I Made Sidja's Dharma Pawayangan palm manuscript samples with significance lies in part II of the manuscript entitled “Tatikas Sapratingkahing Sang Amangku Dalang” consisting of 9 (nine) sheets with coding consisting of numbering (1a) to (9b) showing the contents of various subject and object phrases vocabulary in the context of Balinese traditional wayang kulit performances. The phrases that appear are the names of the gods in Balinese Hindu mythology; spells; the pattern of the puppeteer's actions when he is about to start the performance; various names of wayang accompaniment percussion; variety of wayang performance apparatus; wayang names; stage technique; the ritual of making holy water (tirta) and means of wayang rituals. Second, there are 3 (three) types of language used in the Dharma Pawayangan text, such as; Old Javanese, Sanskrit, and Balinese.